Enigmatic Enemies and the Development of Faith: A Discourse Analysis of Habakkuk - Fuller, David J. (My University, 2018)
The book of Habakkuk is unique amongst the prophetic corpus for its dialogical format, in which an interchange takes place between YHWH and the prophet. Throughout the different sections, reference is made to antagonists both in Judah and Babylon, and it is not always clear which enemy is in view or how the two parties relate. Additionally, the shifts in literary types and overall themes throughout the work have raised the question of how the different sections relate to each other. Towards this end, this dissertation develops a model for discourse analysis of Biblical Hebrew within the framework of Systemic Functional Linguistics, which has a three-level model of meaning. The Mode component tracks the references to entities that create cohesion. The Field component examines what the various participants are doing, tracking process types, transitivity, and logical relations between clauses. The Tenor component looks at the speech roles and subjects used by different speakers. As much as possible, the individual data points within the three types of analysis are correlated with the others in order to discern patterns of usage. The analytical procedure is carried out on each pericope of the book separately, and then the results for each section are compared in order to determine how the successive speeches function as responses to each other, and to better understand development or change in the perspectives of the various speakers throughout. While the large amount of data compiled makes it difficult to summarize succinctly, in all three analytical categories throughout, differing configurations of the entities of the prophet, YHWH, the Chaldean, the nations, and the natural world show development regarding what holds discourses together, how they portray the actions and power relations, and what they arc discussing overall. When the introductory (1:2^l) and final (3:2-19) discourses of the prophet are compared, the mode, field, and tenor exhibit the following shifts, respectively: (1) a cohesive cluster of YHWH, the prophet, and evil things is replaced by a situation in which YHWH’s cohesive chain interacts with various extensions of his power and the natural world in addition to the prophet and the enemies of his people; (2) a transitivity configuration in which YHWH acts upon the prophet and various evil things act upon benevolent institutions is replaced by a configuration in which YHWH acts upon the earth, nations, the prophet (now in a positive way), and the enemies of the prophet; and (3) a discourse in which the prophet asks questions about YHWH’s passivity and makes statements about the rise of evil is succeeded by a discourse in which the prophet commands YHWH to execute his will, asks rhetorical questions about YHWH’s domination of the turbulent seas, and makes statements about YHWH, the natural world’s trembling response to YHWH, and the consequent emotional state of the prophet.
Keywords: Book of Habakkuk; Systemic Functional Linguistics